Al-Qur’an and Islamic Tolerant: Historical Studies - Nur Faizin Muhith (Pascasarjana Universitas Wahid hasyim Semarang, 2017)
AbstractIn his research on the history of the Holy Qur’an, the writer hasbeen able to show the dimensions of the Qur'anic Islamictolerance and how to establish the acceptance of the other, inthe most sacred of the Muslims, which is related to the words ofGod. It is through the historical approach that the researcherbegan to search until he finds the dimensions of the manydifferent Islamic tolerance aspects that appear through thehistory of the Qur'an and its mysteries. Among these aspects: thediversity and variance in the letters of the Qur’an that camedown from above the seven heavens, and the side of writing onthe types of materials available at the time, and the side of themultitude of synonyms and differences and books written in thestatement, and other dimensions and other important aspects.In summary, Muslims adhere to the principle of consultationeven in matters related to the words of God. They also adhere tothe spirit of religious tolerance that permeates Islam in generaland in the history of Qur’anic Koran in particular.Keywords: muṣḥāf; history of al-Qur’an; tolerant